Maintenance upper surface layer based on steel slag coarse aggregate and preparation method of maintenance upper surface layer

By using the upper layer based on the maintenance of steel residue -based coarse materials in the upper layers of the highway, combined with the composite SBS modified asphalt and the limestone mechanism sand collection material, the problem of differences between the mechanical performance of steel residue and natural stone material, realized the steel residue of the steel residue Resource reuse and asphalt hybrid performance improvement.

CN119371141APending Publication Date: 2025-01-28SHANXI EXPRESSWAY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291312.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the mechanical properties of steel slag and natural stone are quite different, and the preparation parameters of steel slag asphalt mixture are not clear, which affects its application in the restoration of the upper layer of the expressway.

Method used

Develop a layer of maintenance based on the maintenance of steel residue -based coarse materials. By determining the best steel residue mixing and mixture coordination ratio, combined with the composite SBS modified asphalt and limestone mechanism sandy collection, improve the anti -slip of asphalt mixture, and the asphalt mixture, and Abrasion resistance and water stability.

Benefits of technology

The resource and reuse of steel residue solid waste, delay the consumption of natural stone, improve the anti -slip and durability performance of asphalt mixture, and reduce the construction cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of road maintenance materials, and particularly relates to an upper surface layer for maintenance based on steel slag coarse aggregate and a preparation method of the upper surface layer. The upper surface layer for maintenance comprises mineral aggregate and composite SBS modified asphalt; the mineral aggregate comprises mixed coarse aggregate, limestone machine-made sand fine aggregate and mineral powder; the mixed coarse aggregate comprises steel slag and diabase of which the particle diameters are 10-15mm and 5-10mm; the mixing amount of the steel slag coarse aggregate in the mixed coarse aggregate is 25%, 50%, 75% or 100%. The upper surface layer for maintenance based on the steel slag coarse aggregate can be used for maintenance of an original asphalt pavement and repair of an upper surface layer of a waste pavement, and can also be used for local damage repair and maintenance of asphalt pavement of a bridge floor, and the paved upper surface layer for maintenance of the steel slag coarse aggregate has good water sealing and anti-sliding effects. The method is low in cost, convenient to construct and suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road maintenance materials, and in particular relates to a maintenance top layer based on steel slag coarse aggregate and a preparation method thereof. Background Art

[0002] Currently, highway construction consumes a significant amount of sand and gravel annually. Excessive rock mining creates a significant environmental burden, and high-quality natural aggregates face a supply-demand imbalance. High-quality stone materials such as limestone and basalt are being consumed at a rapid rate. As stone depletion continues, limestone will become a more valuable resource than coal. Steel slag is a major solid waste generated by the steel industry, accounting for over 13% of raw steel production. However, the comprehensive utilization rate of steel slag is only 20%. Currently, road construction is a major avenue for its comprehensive utilization.

[0003] Industrially produced steel slag is highly alkaline and has a rough, porous surface, which allows for good adhesion to weakly acidic asphalt. Coating with asphalt can, to a certain extent, prevent the hydration and volume expansion of the steel slag, thereby improving the water stability of the asphalt mixture. Furthermore, steel slag has good angularity, high strength, and wear resistance. Applying steel slag to asphalt mixtures improves the wear and skid resistance of the asphalt mixture, and enhances the durability and safety of asphalt pavements. Therefore, using steel slag to replace some or all of the aggregate in the preparation of asphalt concrete not only recycles the steel slag but also reduces the cost of raw materials. Furthermore, increasing the utilization rate of steel slag in road construction can avoid the over-exploitation of natural aggregates, thereby protecting the natural ecological environment and promoting the sustainable development of road construction.

[0004] However, steel slag and natural stone are quite different, and their mechanical properties are also quite different. Clarifying the main preparation parameters of steel slag asphalt mixture and exploring the compounding ratio of steel slag and natural stone are the key to the material composition design of steel slag asphalt mixture.

[0005] Therefore, it is of great significance to develop a curing top layer based on steel slag coarse aggregate and study its preparation method. Summary of the Invention

[0006] Purpose of the invention: The technical problem to be solved by the present invention is to address the deficiencies of the existing technology and provide a maintenance top layer based on steel slag coarse aggregate and a preparation method thereof, apply steel slag solid waste to the repair and maintenance of the top layer of highway road surfaces for major and medium repairs, partially replace diabase, delay the consumption of high-quality natural stone, clarify the performance requirements of the mixture suitable for the repair and maintenance of the top layer of highways, carry out material composition design, determine the optimal steel slag dosage and the optimal mixture ratio, and utilize the anti-skid and wear-resistant advantages of steel slag to improve the anti-skid and durability of the top layer. At the same time, steel slag is compounded with diabase and limestone aggregates to improve the water stability of steel slag asphalt mixture, thereby realizing the resource recycling of steel slag solid waste.

[0007] In order to solve the above technical problems, the present invention discloses a curing top layer based on steel slag coarse aggregate, comprising mineral material and composite SBS modified asphalt;

[0008] The mineral materials include mixed coarse aggregate, limestone machine-made sand fine aggregate and limestone slag;

[0009] The mixed coarse aggregate includes steel slag and diabase with particle diameters of 10-15 mm and 5-10 mm respectively.

[0010] Among them, the mass proportions of each component in the mineral material are 48 to 53 parts of mixed coarse aggregate, 45 to 48 parts of limestone machine-made sand fine aggregate and 2 to 4 parts of mineral powder; among them, the total mass proportions of the mixed coarse aggregate, limestone machine-made sand fine aggregate and limestone mineral powder are 100 parts.

[0011] The steel slag is medium-alkalinity slag; the free total calcium content of the steel slag aggregate is less than 3%, and the average water expansion rate is 0.81%.

[0012] Preferably, the basicity of the steel slag is calculated as follows: Steel slag is mainly composed of five components: calcium oxide, iron oxide, silicon dioxide, magnesium oxide, and aluminum oxide, and these five components account for 83.98% of the total composition. The quaternary basicity of the steel slag aggregate calculated by basicity formula (1) is 2.28, which is a medium basicity slag.

[0013]

[0014] The raw materials of the composite SBS modified asphalt include the following components in parts by mass: 85-90 parts of base asphalt, 15-20 parts of 40-60 mesh rubber powder, and 2-4 parts of SBS.

[0015] The ore material is of AC-13 grading type; the content of steel slag coarse aggregate in the mixed coarse aggregate is 25%, 50%, 75% or 100%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 25%, the optimal oil-stone ratio of the curing upper layer is 5.0%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 50%, the optimal oil-stone ratio of the curing upper layer is 5.1%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 75%, the optimal oil-stone ratio of the curing upper layer is 5.3%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 100%, the optimal oil-stone ratio of the curing upper layer is 5.6%;

[0016] Preferably, when the content of steel slag coarse aggregate in the mixed coarse aggregate is 25%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 7.3%, 5-10mm steel slag accounts for 7.2%, 10-15mm diabase accounts for 18.2%, 5-10mm diabase accounts for 18%, and limestone machine-made sand accounts for 49.3%; the gradation range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 94 .5%, the pass rate range of standard sieve hole 9.5mm is 74.5%, the pass rate range of standard sieve hole 4.75mm is 49.3%, the pass rate range of standard sieve hole 2.36mm is 34.4%, the pass rate range of standard sieve hole 1.18mm is 24.3%, the pass rate range of standard sieve hole 0.6mm is 14.5%, the pass rate range of standard sieve hole 0.3mm is 9.5%, the pass rate range of standard sieve hole 0.15mm is 5.8%, and the pass rate range of standard sieve hole 0.075mm is 3.7%;

[0017] Preferably, when the content of steel slag coarse aggregate in the mixed coarse aggregate is 50%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 14.1%, 5-10mm steel slag accounts for 14.1%, 10-15mm diabase accounts for 11.8%, 5-10mm diabase accounts for 11.7%, and limestone machine-made sand accounts for 48.3%; the gradation range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 94.5%, the pass rate range of standard sieve aperture 9.5mm is 74.1%, the pass rate range of standard sieve aperture 4.75mm is 48.3%, the pass rate range of standard sieve aperture 2.36mm is 33.7%, the pass rate range of standard sieve aperture 1.18mm is 24.2%, the pass rate range of standard sieve aperture 0.6mm is 17.3%, the pass rate range of standard sieve aperture 0.3mm is 12.2%, the pass rate range of standard sieve aperture 0.15mm is 9.1%, and the pass rate range of standard sieve aperture 0.075mm is 5.5%;

[0018] Preferably, when the content of steel slag coarse aggregate in the mixed coarse aggregate is 75%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 20.7%, 5-10mm steel slag accounts for 20.6%, 10-15mm diabase accounts for 5.7%, 5-10mm diabase accounts for 5.7%, and limestone machine-made sand accounts for 47.3%; the gradation range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 9 4.4%, the pass rate range of standard sieve aperture 9.5mm is 73.6%, the pass rate range of standard sieve aperture 4.75mm is 47.3%, the pass rate range of standard sieve aperture 2.36mm is 33.1%, the pass rate range of standard sieve aperture 1.18mm is 23.8%, the pass rate range of standard sieve aperture 0.6mm is 17.1%, the pass rate range of standard sieve aperture 0.3mm is 12.2%, the pass rate range of standard sieve aperture 0.15mm is 9.1%, and the pass rate range of standard sieve aperture 0.075mm is 5.6%;

[0019] Preferably, when the content of steel slag coarse aggregate in the mixed coarse aggregate is 100%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 27.1%, 5-10mm steel slag accounts for 26.9%, and limestone machine-made sand accounts for 46.1%; the gradation range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 94.2%, and the pass rate range of the standard sieve hole 9.5mm is 100%. The pass rate range is 72.9%, the pass rate range of standard sieve aperture 4.75mm is 46.1%, the pass rate range of standard sieve aperture 2.36mm is 32.2%, the pass rate range of standard sieve aperture 1.18mm is 23.1%, the pass rate range of standard sieve aperture 0.6mm is 16.5%, the pass rate range of standard sieve aperture 0.3mm is 11.7%, the pass rate range of standard sieve aperture 0.15mm is 8.7%, and the pass rate range of standard sieve aperture 0.075mm is 5.2%;

[0020] More preferably, in some embodiments of the present invention, road performance testing was conducted on curing top layers containing 0%, 25%, 50%, 75%, and 100% steel slag coarse aggregate in the mixed coarse aggregate. Comprehensive analysis revealed that a steel slag content of 75% resulted in the best high-temperature and water stability of the asphalt mixture, while also meeting regulatory requirements for fatigue performance, volume stability, low-temperature crack resistance, and anti-skid performance. Therefore, the recommended steel slag content is 75%.

[0021] The present invention also discloses a method for preparing a curing top layer based on steel slag coarse aggregate, the specific steps of which are: heating and drying the steel slag coarse aggregate, diabase coarse aggregate, limestone machine-made sand fine aggregate, and limestone mineral powder, and then fully mixing and stirring; then adding a certain amount of composite SBS modified asphalt, maintaining the stirring speed at 60 r / min for 5 to 10 minutes, and the temperature of the mixed material being mixed and discharged at 175-180°C; then quickly spreading it on the road surface, and the spreading temperature being not lower than 160°C; after the curing of the mixture is completed, forming a 4 cm thick layer of steel slag asphalt concrete on the road surface for top layer repair and curing.

[0022] Beneficial Effects: Steel slag, a solid waste product from steelmaking, is not only wear-resistant and well-shaped, but also exhibits excellent adhesion to asphalt. Using steel slag to replace a portion of aggregate, combined with composite modified asphalt and other materials, to create a curing top layer based on steel slag coarse aggregate offers significant cost advantages over other curing top layers and is suitable for large-scale deployment.

[0023] The present invention's asphalt mixture for the top layer contains steel slag in five different proportions: 25%, 50%, 75%, and 100%. The optimal steel slag proportion is 75%. The addition of steel slag effectively reduces the over-exploitation of diabase coarse aggregate and limestone fine aggregate. The steel slag asphalt mixture saves approximately 5.5% per kilometer of paving costs compared to diabase asphalt mixtures. Some road performance characteristics are significantly superior to diabase asphalt mixtures. Furthermore, the mixture recycles waste resources, resulting in significant socioeconomic benefits.

[0024] The method for preparing the maintenance top layer based on steel slag coarse aggregate provided by the present invention is not only suitable for the maintenance of asphalt pavements, but can also be used for the rapid repair of waste pavements to prevent serious pavement diseases. It can also be used for local damage repair and preventive maintenance of bridge asphalt pavements, improve surface functions, and extend the service life of the pavement. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more apparent.

[0026] Figure 1 This is a photo of the 75% steel slag asphalt mixture prepared in Example 5 of the present invention;

[0027] Figure 2 This is a volume index relationship diagram of test pieces with different oil-stone ratios at 0% addition in Example 4 of the present invention;

[0028] Figure 3 This is a relationship diagram of volume indices of test pieces with different asphalt-stone ratios at 25% addition in Example 4 of the present invention;

[0029] Figure 4This is a volume index relationship diagram of test pieces with different oil-stone ratios at 50% addition in Example 4 of the present invention;

[0030] Figure 5 This is a relationship diagram of volume indices of test pieces with different asphalt-stone ratios at 75% addition in Example 4 of the present invention;

[0031] Figure 6 This is a relationship diagram of volume indices of test pieces with different oilstone ratios and 100% admixture in Example 4 of the present invention. DETAILED DESCRIPTION

[0032] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0033] In order to make the technical means, innovative features, objectives and effects achieved by the present invention easier to understand, the present invention is further described below with reference to specific embodiments.

[0034] Example 1:

[0035] A curing top layer based on steel slag coarse aggregate includes the following raw materials: composite SBS modified asphalt, 10-15mm and 5-10mm diabase and steel slag coarse aggregate, 0.075-3mm limestone machine-made sand fine aggregate, and 0-0.075 limestone mineral powder. According to the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004), the properties of the raw materials, including asphalt, fine aggregate, coarse aggregate, and mineral powder, were tested:

[0036] (1) Asphalt

[0037] The asphalt used is ID-grade SBS modified asphalt produced in Shanxi. Its performance meets the technical requirements, the heavy-load characteristics of Shanxi roads and the principle of using local materials. The test results of its performance indicators are shown in Table 1:

[0038] Table 1 Technical properties of modified asphalt

[0039]

[0040] (2)Fine aggregate

[0041] The fine aggregate used is manufactured sand made from limestone produced in Shanxi. Its performance indicators meet the technical requirements, satisfy the principle of using local materials, and reduce the total cost of the test section construction project. The performance index test results are shown in Table 2:

[0042] Table 2 Technical parameters of fine aggregate

[0043]

[0044] (3) Coarse aggregate

[0045] The coarse aggregates used are steel slag aggregate produced by Taiyuan Iron and Steel and diabase produced in Shanxi. The specifications are 10-15mm and 5-10mm respectively, which meet the technical requirements. The performance index test results are shown in Table 3:

[0046] Table 3 Technical parameters of coarse aggregate

[0047]

[0048] (4) Mineral powder

[0049] The mineral powder used is limestone mineral powder produced in Shanxi, which meets the technical requirements, satisfies the principle of using local materials, and reduces the total cost of the test section construction project. The performance index test results are shown in Table 4:

[0050] Table 4 Technical parameters of mineral powder

[0051]

[0052] The raw materials include 48 to 53 parts of steel slag and diabase coarse aggregate (4.75-16 mm), 45 to 48 parts of limestone machine-made sand fine aggregate (0.075-4.75 mm), and 2 to 4 parts of limestone slag (0-0.075 mm). The total weight of the coarse aggregate, fine aggregate, and slag is 100 parts.

[0053] Example 2:

[0054] As a steelmaking product, steel slag has a formation mode and chemical composition that are quite different from natural stones such as diabase. In order to clarify the basic chemical composition of steel slag aggregate, a fluorescence spectrometer was used to conduct XRF tests. The test covers all elements from nitrogen (7) to uranium (92). The maximum power of the X-ray tube is not less than 4.2kW, and the content determination range is ppm to 100%. Table 5 shows the XRF analysis results of steel slag aggregate and diabase aggregate. The results show that the main components of the steel slag aggregate used are calcium oxide, iron oxide, silicon dioxide, magnesium oxide and aluminum oxide. These five components account for 83.98% of the total components of the steel slag aggregate, among which the chemical form with the highest content is calcium oxide (accounting for 38.94%). The main components of the diabase aggregate are calcium oxide, iron oxide, silicon oxide and aluminum oxide. These four components account for 88.62% of the total components of the diabase aggregate, among which the chemical component with the highest content is silicon dioxide (accounting for 53.27%). The contents of calcium oxide, iron oxide and silicon dioxide in the two aggregates are quite different, and the main reason may be related to the slag-making materials and slag-forming process of steel slag.

[0055] Table 5 Test results of chemical composition of steel slag

[0056]

[0057] The acidity and alkalinity of the aggregate are determined by analyzing the content of silica in the aggregate. When the silica content is less than 53%, it is alkaline, when it is 52% to 65%, it is neutral, and when it is greater than 65%, it is acidic. The silica content in the steel slag aggregate is 15.31%, and the silica content in the diabase aggregate is 53.27%. Therefore, it can be seen that the steel slag aggregate is alkaline aggregate and the diabase aggregate is neutral aggregate. In order to clarify the alkalinity of the steel slag aggregate, the alkalinity value of the steel slag aggregate is further calculated. Alkalinity refers to the ratio of the percentage content of alkaline oxides to acidic oxides in the sintered ore. Since the chemical composition of steel slag aggregate is relatively rich, the quaternary alkalinity is used to quantitatively evaluate its alkalinity. The calculation formula is shown in formula (1). Substituting the chemical composition of steel slag into formula (1), it can be seen that the quaternary alkalinity of steel slag aggregate is 2.28, which is within the range of 1.8 to 2.5 and belongs to medium alkalinity aggregate.

[0058]

[0059] Example 3:

[0060] Before use in road construction, to determine whether the volume stability of steel slag meets regulatory requirements, two methods were used: measuring the free calcium oxide content in the slag and measuring the slag's water expansion rate. The free calcium oxide content was determined for slag with particle sizes ranging from 3 to 5 mm and 10 to 15 mm. The slag required for the test was magnetically separated, and only non-magnetic materials were tested. The results of the free total calcium content of the slag are shown in Table 6:

[0061] Table 6 Determination results of free total calcium content in steel slag

[0062]

[0063] The above tests measured the free total calcium (f-CaO + Ca(OH)2) content of steel slag of two particle sizes. As can be seen from Table 6, the free total calcium content of steel slag aggregates of both specifications is less than 3%, that is, the free calcium oxide content is less than 3%, which meets the maximum content requirement of 3% in the "Technical Specification for Highway Asphalt Pavement Construction" (JTG F40-2004).

[0064] According to the steel slag immersion expansion rate test method in GB / T 24175, the steel slag specimen’s immersion expansion rate increased rapidly in the first two days, and tended to stabilize after eight days. On the tenth day, the immersion expansion rates of the steel slag specimens were 0.82%, 0.81%, and 0.80%, respectively. The final immersion expansion rate of the steel slag used was 0.81%, which met the requirement of less than 2% in the specification, ensuring the expansion stability of the steel slag raw material during use.

[0065] Example 4:

[0066] The raw materials for the composite SBS-modified asphalt include the following components, by weight: 85-90 parts base asphalt, 15-20 parts 40-60 mesh rubber powder, and 2-4 parts SBS. The steel slag asphalt mixture uses an AC-13 aggregate gradation, with coarse steel slag aggregate content of 0%, 25%, 50%, 75%, and 100%. The optimal oil-to-stone ratios are 4.9%, 5.0%, 5.1%, 5.3%, and 5.6%, respectively.

[0067] By adjusting the grading curve multiple times, the initial mix ratio of the diabase asphalt mixture aggregate was obtained. According to the selected mix ratio, the content of steel slag coarse aggregate was 0%, diabase was used as coarse aggregate, and machine-made sand was used as fine aggregate. At this time, the mix ratio of AC-13 diabase asphalt mixture is shown in Table 7.

[0068] Table 7AC-13 Diabase Asphalt Mixture Proportions

[0069]

[0070] Based on experience, the five oil-stone ratios of the 0% steel slag test group were selected as 4.5%, 4.8%, 5.1%, 5.4%, and 5.7%. The bulk density (ρ f The volume parameters of the steel slag asphalt mixture are calculated by measuring the volume parameters such as the void ratio (VV), effective asphalt saturation (VFA), and aggregate void ratio (VMA). The stability (MS) and flow value (FL) of the specimen are then measured. The volume parameters of the steel slag asphalt mixture are shown in Table 8.

[0071] Table 8 Volume parameter test results

[0072]

[0073] With the asphalt mixture asphalt aggregate ratio as the horizontal axis and the gross volume density, VV, VMA, VFA, MS, and FL as the vertical axis, a relationship diagram of the volume indexes of specimens with different asphalt aggregate ratios is drawn, such as Figure 2 As shown, according to JTG 20F40-2004, OAC1 is 4.8%, OAC2 is 5.0%, and OAC is 4.9. Therefore, the optimal asphalt content of asphalt mixture with 0% steel slag content is 4.9%.

[0074] According to the selected mix ratio of diabase asphalt mixture, 25% steel slag coarse aggregate is added in equal proportions, the remaining coarse aggregate is all diabase, and the fine aggregate is machine-made sand. At this time, the mix ratio of AC-13 steel slag asphalt mixture is shown in Table 9.

[0075] Table 9 Mix proportion of 25% AC-13 steel slag asphalt mixture

[0076]

[0077] Considering the porous surface and high water absorption of steel slag, five oil-to-stone ratios of 4.6%, 4.9%, 5.2%, 5.5%, and 5.8% were selected for the 25% steel slag content test group. The bulk density, VV, VFA, VMA, and other volumetric parameters of the specimens were calculated according to JTG E20-2011 T0705. The MS and FL of the specimens were then measured. The volumetric parameters are shown in Table 10.

[0078] Table 10 Volume parameter test results

[0079]

[0080]

[0081] With the asphalt mixture asphalt aggregate ratio as the horizontal axis and the gross volume density, VV, VMA, VFA, MS, and FL as the vertical axis, a relationship diagram of the volume indexes of specimens with different asphalt aggregate ratios is drawn, such as Figure 3 As shown, according to JTG 20F40-2004, OAC1 is 5.0%, OAC2 is 5.0%, and OAC is 5.0. Therefore, the optimal asphalt content of 25% steel slag asphalt mixture is 5.0%.

[0082] According to the selected mix ratio of diabase asphalt mixture, 50% steel slag coarse aggregate is added in equal proportions, the remaining coarse aggregate is all diabase, and the fine aggregate is machine-made sand. At this time, the mix ratio of AC-13 steel slag asphalt mixture is shown in Table 11.

[0083] Table 11 Grading of 50% AC-13 steel slag asphalt mixture

[0084]

[0085] Considering the porous surface and high water absorption of steel slag, five oil-to-aggregate ratios of 4.7%, 5.0%, 5.3%, 5.6%, and 5.9% were selected for the 50% steel slag content test group. The water-based and surface-dry weights of the asphalt mixture specimens were measured according to JTG E20-2011 T0705. The bulk density, VV, VFA, and VMA of the specimens were calculated. The MS and FL values ​​of the specimens were then measured using the Marshall test. The bulk parameters of the steel slag asphalt mixture are shown in Table 12.

[0086] Table 12 Marshall specimen volume parameters for determining asphalt dosage

[0087]

[0088] With the asphalt mixture asphalt aggregate ratio as the horizontal axis and the gross volume density, VV, VMA, VFA, MS, and FL as the vertical axis, a relationship diagram of the volume indexes of specimens with different asphalt aggregate ratios is drawn, such as Figure 4As shown, according to JTG 20F40-2004, OAC1 is 5.2%, OAC2 is 5.0%, and OAC is 5.1. Therefore, the optimal asphalt content of asphalt mixture with 50% steel slag content is 5.1%.

[0089] According to the selected mix ratio of diabase asphalt mixture, 75% steel slag coarse aggregate is added in equal proportions, the remaining coarse aggregate is all diabase, and the fine aggregate is machine-made sand. At this time, the mix ratio of AC-13 steel slag asphalt mixture is shown in Table 13.

[0090] Table 13 Mix proportions of 75% AC-13 steel slag asphalt mixture

[0091]

[0092] Considering the porous surface and high water absorption of steel slag, five oil-to-stone ratios of 4.8%, 5.1%, 5.4%, 5.7%, and 6.0% were selected for the 75% steel slag content test group. The bulk density, VV, VFA, VMA, and other volumetric parameters of the specimens were calculated according to JTG E20-2011 T0705. The MS and FL values ​​of the specimens were then measured. These volumetric parameters are shown in Table 14.

[0093] Table 14 Volume parameter test results

[0094]

[0095] With the asphalt mixture asphalt aggregate ratio as the horizontal axis and the gross volume density, VV, VMA, VFA, MS, and FL as the vertical axis, a relationship diagram of the volume indexes of specimens with different asphalt aggregate ratios is drawn, such as Figure 5 As shown in the figure, according to JTG 20F40-2004, OAC1 is 5.4%, OAC2 is 5.2%, and OAC is 5.3. Therefore, the optimal asphalt content of asphalt mixture with 75% steel slag content is 5.3%.

[0096] According to the selected mix ratio of diabase asphalt mixture, 100% steel slag coarse aggregate is added in equal proportions, that is, all coarse aggregate is steel slag and fine aggregate is machine-made sand. At this time, the mix ratio of AC-13 steel slag asphalt mixture is shown in Table 15.

[0097] Table 15 Mix proportions of 100% AC-13 steel slag asphalt mixture

[0098]

[0099] Considering the porous surface and high water absorption of steel slag, five asphalt-to-aggregate ratios of 4.8%, 5.1%, 5.4%, 5.7%, and 6.0% were selected for the 100% slag dosage test group. The water-dry weight and surface-dry weight of the asphalt mixture specimens were measured according to JTG E20-2011 T0705. The bulk density, VV, VFA, VMA, and other volumetric parameters of the specimens were calculated. The MS and FL values ​​of the specimens were then measured. These volumetric parameters are shown in Table 16.

[0100] Table 16 Volume parameter test results

[0101]

[0102] With the asphalt mixture asphalt aggregate ratio as the horizontal axis and the gross volume density, VV, VMA, VFA, MS, and FL as the vertical axis, a relationship diagram of the volume indexes of specimens with different asphalt aggregate ratios is drawn, such as Figure 6 As shown in the figure, according to JTG 20F40-2004, OAC1 is 5.6%, OAC2 is 5.6%, and OAC is 5.6. Therefore, the optimal asphalt content of the asphalt mixture with 100% steel slag is 5.6%.

[0103] Example 5:

[0104] The road performance tests were carried out on the AC-13 asphalt mixtures with the five steel slag dosages, and the results are shown in Table 17.

[0105] Table 17 Summary of performance test results of AC-13 steel slag asphalt mixtures with different additions

[0106]

[0107] Table 17 shows that a comprehensive comparison of the road performance of asphalt mixtures with different steel slag content demonstrates that all meet regulatory requirements. When the steel slag content is 75%, the asphalt mixture exhibits optimal high-temperature and water stability, while also meeting regulatory requirements for fatigue performance, volumetric stability, low-temperature crack resistance, and anti-skid performance. Therefore, the recommended steel slag content is 75%.

[0108] The road performance tests include high temperature performance, skid resistance, low temperature crack resistance, fatigue performance, water stability and volume stability.

[0109] Example 6:

[0110] Aggregate heating temperature and mixture mixing temperature should be controlled at 175°C and 180°C, respectively, and the mixing time should be appropriately extended. To ensure the uniformity and construction quality of the asphalt mixture, a dry mix should be performed twice in a mixer before the asphalt mixture is mixed. This improves the efficiency and quality of subsequent asphalt mixing. Several batches of aggregate are dry mixed and discarded before the asphalt mixture is mixed. Construction temperatures are shown in Table 18.

[0111] Table 18 On-site construction temperature control

[0112]

[0113] To ensure that heat loss of steel slag asphalt mixture during transportation is effectively controlled and that its paving temperature can be stably maintained at around 160°C, it is necessary to strengthen insulation measures during transportation. The following two points should be noted:

[0114] ① Before transportation, apply oil-water mixture to the four walls of the carriage to prevent the asphalt mixture from adhering to the carriage.

[0115] ② During transportation, the vehicle must be covered to ensure that the temperature of the steel slag asphalt mixture is around 160°C. The driving speed should be uniform and slow to avoid segregation of the mixture.

[0116] The paving process for steel slag asphalt mixtures differs slightly from that for conventional asphalt mixtures. During on-site paving, ensure the paver is in good condition, control the paving width, and ensure a sufficient number of material transport vehicles. When operating the paver, ensure a smooth start and a constant speed. Construction personnel must ensure the auger rotates steadily, ensure that adjacent paving sections overlap appropriately, and strictly follow the markings to avoid uneven thickness. During the paving of steel slag asphalt mixtures, an appropriate screed vibration frequency and amplitude should be selected to improve the initial compaction of the pavement. Pave slowly, evenly, and continuously to avoid segregation of the mixture. The paving speed should be adjusted to 2-4 m / min based on actual conditions. Elevation control using wire ropes on both sides should be used to control elevation and thickness. If continuous paving is not possible, construction joints should be established.

[0117] The compaction process for steel slag asphalt mixture differs from that for ordinary cement concrete. Due to its high density and hardness, steel slag is more difficult to compact than ordinary stone asphalt mixture. For optimal pavement compaction, an additional pass is recommended. After paving the steel slag asphalt concrete, use a double steel-drum roller for initial compaction, followed by a rubber-drum roller for smoothing, with three passes each. Finally, use a double steel-drum roller for two passes until no visible wheel marks remain.

[0118] The present invention provides a curing top layer based on steel slag coarse aggregate and a method for preparing the same. While there are numerous methods and approaches for implementing this technical solution, the foregoing merely represents a preferred embodiment of the present invention. It should be noted that those skilled in the art may make various improvements and modifications without departing from the principles of the present invention, and such improvements and modifications are also within the scope of protection of the present invention. Any components not specified in this embodiment may be implemented using existing technologies.

Claims

1. A curing top layer based on steel slag coarse aggregate, characterized in that: Including mineral aggregate and composite SBS modified asphalt; The mineral materials include mixed coarse aggregate, limestone machine-made sand fine aggregate and limestone powder; The mixed coarse aggregate includes steel slag and diabase with particle diameters of 10-15 mm and 5-10 mm.

2. The maintenance top layer according to claim 1, characterized in that: The mass proportions of each component in the mineral material are 48 to 53 parts of mixed coarse aggregate, 45 to 48 parts of limestone machine-made sand fine aggregate and 2 to 4 parts of limestone mineral powder; wherein the total mass proportions of the mixed coarse aggregate, limestone machine-made sand fine aggregate and mineral powder are 100 parts.

3. The maintenance top layer according to claim 1, characterized in that: The steel slag is medium-basicity slag; the free total calcium content of the steel slag aggregate is less than 3%, and the average water expansion rate is 0.81%.

4. The maintenance top layer according to claim 1, characterized in that: The raw materials of the composite SBS modified asphalt include the following components in parts by mass: 85-90 parts of base asphalt, 15-20 parts of 40-60 mesh rubber powder, and 2-4 parts of SBS.

5. The maintenance top layer according to claim 1, characterized in that: The mineral material adopts AC-13 mineral material grading type; the content of steel slag coarse aggregate in the mixed coarse aggregate is 25%, 50%, 75% or 100%; wherein, when the content of steel slag coarse aggregate in the mixed coarse aggregate is 25%, the best oil-stone ratio of the upper curing layer is 5.0%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 50%, the best oil-stone ratio of the upper curing layer is 5.1%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 75%, the best oil-stone ratio of the upper curing layer is 5.3%; when the content of steel slag coarse aggregate in the mixed coarse aggregate is 100%, the best oil-stone ratio of the upper curing layer is 5.6%.

6. The maintenance top layer according to claim 5, characterized in that: When the content of steel slag coarse aggregate in the mixed coarse aggregate is 25%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 7.3%, 5-10mm steel slag accounts for 7.2%, 10-15mm diabase accounts for 18.2%, 5-10mm diabase accounts for 18%, and limestone machine-made sand accounts for 49.3%; the grading range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 94.5 %, the pass rate range of standard sieve hole 9.5mm is 74.5%, the pass rate range of standard sieve hole 4.75mm is 49.3%, the pass rate range of standard sieve hole 2.36mm is 34.4%, the pass rate range of standard sieve hole 1.18mm is 24.3%, the pass rate range of standard sieve hole 0.6mm is 14.5%, the pass rate range of standard sieve hole 0.3mm is 9.5%, the pass rate range of standard sieve hole 0.15mm is 5.8%, and the pass rate range of standard sieve hole 0.075mm is 3.7%.

7. The maintenance top layer according to claim 5, characterized in that: When the content of steel slag coarse aggregate in the mixed coarse aggregate is 50%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 14.1%, 5-10mm steel slag accounts for 14.1%, 10-15mm diabase accounts for 11.8%, 5-10mm diabase accounts for 11.7%, and limestone machine-made sand accounts for 48.3%; the grading range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 94 .5%, the pass rate range of standard sieve hole 9.5mm is 74.1%, the pass rate range of standard sieve hole 4.75mm is 48.3%, the pass rate range of standard sieve hole 2.36mm is 33.7%, the pass rate range of standard sieve hole 1.18mm is 24.2%, the pass rate range of standard sieve hole 0.6mm is 17.3%, the pass rate range of standard sieve hole 0.3mm is 12.2%, the pass rate range of standard sieve hole 0.15mm is 9.1%, and the pass rate range of standard sieve hole 0.075mm is 5.5%.

8. The maintenance top layer according to claim 5, characterized in that: When the content of steel slag coarse aggregate in the mixed coarse aggregate is 75%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 20.7%, 5-10mm steel slag accounts for 20.6%, 10-15mm diabase accounts for 5.7%, 5-10mm diabase accounts for 5.7%, and limestone machine-made sand accounts for 47.3%; the grading range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, and the pass rate range of the standard sieve hole 13.2mm is 94. 4%, the pass rate range of standard sieve hole 9.5mm is 73.6%, the pass rate range of standard sieve hole 4.75mm is 47.3%, the pass rate range of standard sieve hole 2.36mm is 33.1%, the pass rate range of standard sieve hole 1.18mm is 23.8%, the pass rate range of standard sieve hole 0.6mm is 17.1%, the pass rate range of standard sieve hole 0.3mm is 12.2%, the pass rate range of standard sieve hole 0.15mm is 9.1%, and the pass rate range of standard sieve hole 0.075mm is 5.6%.

9. The maintenance top layer according to claim 5, characterized in that: When the content of steel slag coarse aggregate in the mixed coarse aggregate is 100%, the proportions of the components in the AC-13 ore are as follows: 10-15mm steel slag accounts for 27.1%, 5-10mm steel slag accounts for 26.9%, and limestone machine-made sand accounts for 46.1%; the gradation range of the AC-13 ore is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 94.2%, and the pass rate range of the standard sieve hole 9.5mm is The pass rate range of standard sieve hole 4.75mm is 46.1%, the pass rate range of standard sieve hole 2.36mm is 32.2%, the pass rate range of standard sieve hole 1.18mm is 23.1%, the pass rate range of standard sieve hole 0.6mm is 16.5%, the pass rate range of standard sieve hole 0.3mm is 11.7%, the pass rate range of standard sieve hole 0.15mm is 8.7%, and the pass rate range of standard sieve hole 0.075mm is 5.2%.

10. The method for preparing a curing top layer according to any one of claims 1 to 9, characterized in that: The specific steps are: heat and dry steel slag coarse aggregate, diabase coarse aggregate, limestone machine-made sand fine aggregate and limestone mineral powder, then mix and stir them thoroughly; then add a certain amount of composite SBS modified asphalt, maintain stirring at a speed of 60r / min for 5 to 10 minutes, and the temperature of the mixed material should be 175-180℃; then quickly spread it on the road surface, and the spreading temperature should not be lower than 160℃; after the mixture is cured, form a 4cm thick layer of steel slag asphalt concrete on the road surface for upper layer repair and maintenance.